Continuous Endotracheal Tube Cuff Pressure Control Decreases Incidence of Ventilator-Associated Pneumonia in Patients with Traumatic Brain Injury. Issue 3 (7th February 2022) - Sevdi, Mehmet Salih; Demirgan, Serdar; Erkalp, Kerem; Akyol, Onat; Ozcan, Funda Gumus; Guneyli, Hasan Cem; Tunali, Mehmet Can; Selcan, Aysin
Abstract: Background: Ventilator-associated pneumonia (VAP) is a common cause of morbidity and mortality in intensive care unit (ICU), and among the several preventative strategies described to reduce the incidence of VAP, the most important is the endotracheal tube cuff (ETC) pressure. The present study was conducted on 60 patients who required mechanical ventilation (MV) in the ICU with traumatic brain injury (TBI). Methods: The patients were randomized into two groups of 30, in which ETC pressure was regulated using a smart cuff manager (SCM) (Group II), or manual measurement approach (MMA) (Group I). Demographic data, MV duration, length of ICU stay and mortality rates were recorded. The clinical pulmonary infection scores (CPISs), C-reactive protein (CRP) values, and the fraction of inspired oxygen (FiO2) and positive end-expiratory pressure (PEEP) values of the groups were compared at baseline, and at hours 48, 72 and 96. Results: In Group I, CPIS values significantly higher than Group II in 48th, 72nd and 96th hours ( p < 0.05). In Group I, PEEP values and deep tracheal aspirate (DTA) culture growth rates significantly higher than Group II in 72nd and 96th hours ( p < 0.05). Conclusion: The continuous maintenance of ETC pressure using SCM reduced the incidence of VAP.